Measuring the Acceleration of a Motorcycle - Slepanek, Petr (European Scientific Journal, ESJ, 2018)
The paper describes problems of measuring the acceleration of a motorcycle. Measured motorcycle was traveling Honda CBR 1000 F. Measurement was realized at a parking area with use of the two-axis accelerometer XL METRTM PRO GAMMA. The aim of the measurement was to determine the speed of acceleration at the normal (not fast, not slow) starting of the motorcycle at the first, second and third gears, followed by stabilization of the speed to the value required for urban traffic. Motorcycle acceleration values followed by the speed stabilization at 40 km/h ranged from 1.8 to 2.1 m.s-2 . Motorcycle acceleration values followed by the speed stabilization at 50 km/h ranged from 1.9 to 2.2 m.s-2 . Motorcycle acceleration values followed by the speed stabilization at 60 km/h ranged from 2.1 to 2.2 m.s-2 . Achieved acceleration values were in the range from 1.8 to 2.2 m.s -2 . Individual results of the measurement have been summarized in the tables and graphs. Technically acceptable parameters for motorcycle acceleration are not many, so the measured data in this article could be useful to experts forsolving traffic accidents with the presence of a motorcycle.